Dental students’ awareness and attitudes toward HPV-related oral cancer: a cross sectional study at the University of Jordan - Sallam, Malik; Al-Fraihat, Esraa; Dababseh, Deema; Yaseen, Alaa’; Taim, Duaa; Zabadi, Seraj; Hamdan, Ahmad A.; Hassona, Yazan; Mahafzah, Azmi; Şahin, Gülşen Özkaya (BMC oral health, 2019)
The incidence of human papilloma virus (HPV)-related oral cancer has recently increased worldwide. The role of dentists is of prime importance in the early detection of oral cancer which would result in a favourable outcome for the patients. The aim of the current study was to assess the knowledge, awareness and attitudes of dental students, interns and postgraduate maxillofacial residents at the University of Jordan (UJ) to different aspects of oral cancer, particularly those related to HPV. A paper-based survey was conducted at UJ among all pre-clinical dental students (pre-clinical group), clinical dental students, interns and postgraduate maxillofacial residents (clinical group). The survey included five sections comprising 29 items. The sections included questions investigating oral cancer knowledge, oral cancer screening, HPV knowledge and the ability to discuss personal topics with patients. A total of 376 respondents out of 1052 potential participants completed at least one item of the survey (study coverage of 35.7%). Among the study participants, the pre-clinical group represented 41.2% (n = 155) and the clinical group represented 58.8% (n = 221). The majority of participants in the clinical group showed better knowledge on oral cancer potential anatomic sites, clinical presentation and possible risk factors compared to the pre-clinical group. Most participants in the clinical group (n = 195, 88.2%) correctly identified HPV as a risk factor for oral cancer development. The majority of participants in the clinical group displayed suitable attitude towards oral cancer screening despite their desire for a reliable screening device and additional training in oral cancer screening. A number of limitations in basic knowledge about HPV was noticed among participants in the clinical group particularly related to unawareness of the vaccine availability. The majority of participants in the clinical group displayed hesitancy in discussing personal topics with the patients, including the history of previous sexually transmitted infections and sexual abuse. Gaps in knowledge regarding HPV-related oral cancer has been detected which necessitate intervention measures including curricular changes, training workshops and awareness campaigns.